12 The potential for eye donationfrom hospice and palliative care clinical settings in England – a retrospective case notes review of deceased patient records. (16th November 2022) - Long-Sutehall, Tracy; Bracher, Mike; Madi-Segwagwe, Banyana Cecile; Faull, Christina; Hurlow, Adam; Mollart, Sarah; Rayment, Clare; Short, Jill; Wale, Jane; Brown, Mark; Winstanley, Emma; Jacob, Faith; et al.
Abstract : Background: There is a need to identify additional routes of supply for ophthalmic tissue in the UK due to deficits between supply and demand. In response to this need the NIHR funded study, Eye Donation from Palliative and Hospice Care: Investigating Potential, Practice, Preference, and Perceptions) (EDiPPPP) project was developed in partnership with NHSBT Tissue Services ( now Organ Tissue Donation and Transplantation). Aim: This presentation will report findings from work package one of EDiPPPP which aimed to: scope the size and clinical characteristics of the potential eye donation (ED) population via a large-scale, multi-site retrospective case notes review across England establishing: the size of the potential ED population; describe the clinical characteristics of the potential ED population and identify challenges for clinicians in applying the standard ED criteria for assessing patient eligibility. Results: Retrospective review of 1200 deceased patient case notes (600 HPC; 600 HPCS) by reviewers (healthcare professionals) at research sites against current ED criteria were then evaluated by specialists based at the National Health Service Blood and Transplant Tissue services (NHSBT-TS). Note review established that 46% (n=553) of 1200 deceased patients notes were agreed as eligible for eye donation (total cases Hospice care settings = 56% (n=337); Palliative care settings = 36% (n=216) with only 1.2% of potential donors referred to NHSBT-TS for eye donation (Hospice care settings = 1.2% (n=4); Palliative care settings = 1.3% (n=3). Application of the eye donation criteria resulted in an 81% agreement rate outcome for all sites (HPC = 79.2%; HPCS = 82.8%). If cases where there was a difference of assessment but where NHSBT evaluation indicated eligibility are included (n=113) the potential donor pool rises from 553 (46.1% total cases) to 666 (56%) eligible cases. Conclusions: Significant potential exists for eye donation from the clinical sites in this study. This potential is not currently being realised. In view of the predicted increase in need for ophthalmic tissue it is essential that the potential route to increase the supply of ophthalmic tissue demonstrated in this retrospective note review is accessed. The presentation will conclude with recommendations for service development.